Counseling needs of students in the Institute of Physical Education, Mostaganem University (Algeria) - Djamel Mokrani; Houcine Benzidane; Ahmed Ataalah; Fateh Zereg (Nicolaus Copernicus University in Toruń, 2020)
In the light of researches aim knowing the counselling needs for students of Institute of Physical Education and Sport, University of Abdel Hamid Ibn Badis Mostaganem (Algeria), the researcher suggest that there are many counselling needs for students this Institute, so the researcher choose the sample by using random level method of (480) students  divided into two samples for building and applying uses, to achieve goals of research the researcher build research tool represented by showing counselling needs consisted of (7) fields of (81) items, placing in front of each one three replacements (always, sometime, never) then correct them by giving marks  as (1,2,3) respectively, then the researcher analyzes counselling needs in its final form on applying sample of (120) students  (male and female) for students Institute of Physical Education and Sport, University of Abdel Hamid Ibn Badis Mostaganem. After treating the results statistically, results showed that there are (38) counselling needs should be saturated inside the students of Institute. In the lights of research's results the researcher insisted on taking the advantages of studying counselling needs for students of physical education institute in developing counselling programs in the Institute and build it on a scientific bases emanated from a real needs of students.